The dipeptide Phe-Phe amide attenuates signs of hyperalgesia, allodynia and nociception in diabetic mice using a mechanism involving the sigma receptor system - Ohsawa Masahiro; Carlsson Anna; Asato Megumi; Koizumi Takayuki; Nakanishi Yuki; Fransson Rebecca; Sandström Anja; Hallberg Mathias; Nyberg Fred; Kamei Junzo (SAGE Publishing, 2011)
Abstract Background Previous studies have demonstrated that intrathecal administration of the substance P amino-terminal metabolite substance P1-7 (SP1-7) and its C-terminal amidated congener induced antihyperalgesic effects in diabetic mice. In this study, we studied a small synthetic dipeptide related to SP1-7 and endomorphin-2, i.e. Phe-Phe amide, using the tail-flick test and von Frey filament test in diabetic and non-diabetic mice. Results Intrathecal treatment with the dipeptide increased the tail-flick latency in both diabetic and non-diabetic mice. This effect of Phe-Phe amide was significantly greater in diabetic mice than non-diabetic mice. The Phe-Phe amide-induced antinociceptive effect in both diabetic and non-diabetic mice was reversed by the σ1 receptor agonist (+)-pentazocine. Moreover, Phe-Phe amide attenuated mechanical allodynia in diabetic mice, which was reversible by (+)-pentazocine. The expression of spinal σ1 receptor mRNA and protein did not differ between diabetic mice and non-diabetic mice. On the other hand, the expression of phosphorylated extracellular signal-regulated protein kinase 1 (ERK1) and ERK2 proteins was enhanced in diabetic mice. (+)-Pentazocine caused phosphorylation of ERK1 and ERK2 proteins in non-diabetic mice, but not in diabetic mice. Conclusions These results suggest that the spinal σ1 receptor system might contribute to diabetic mechanical allodynia and thermal hyperalgesia, which could be potently attenuated by Phe-Phe amide.